Ligand Exchange Inducing Efficient Incorporation of CisPt Derivatives into Ureasil-PPO Hybrid and Their Interactions with the Multifunctional Hybrid Network - Molina, Eduardo F. [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Briois, Valerie (Amer Chemical Soc, 2012)
Efficient incorporation of (PtCl3EtOH)(-) anion derived from CisPt moiety into ureasil-PPO (poly(propylene oxide)) network was achieved from one-pot sol-gel synthesis carried out in the presence of water, HCl, and ethanol. Reactant proportion was adequately chosen to lead the sol-gel formation of siloxane nodes at the end of short PPO chains, to prevent the CisPt hydrolysis, and to induce platinum ligand exchange. The efficient dissolution of Pt species and the formation of a homogeneous liquid like solution on the transparent and elastomeric ureasil-PPO hybrid were evidenced by differential scanning calorimetry and small-angle X-ray scattering. The CisPt ligand exchange and the formation of a Zeise-type salt Y+(PtCl3R)(-) were demonstrated by Raman spectroscopy and Pt L-3-edge EXAFS analysis. In light of these results and in agreement with the proportion of reactants introduced in the media for synthesis and those self produced by hydrolysis and condensation processes, we proposed for R the ethanol moiety and for Y the ammonium cation. The Raman spectroscopy studies indicated also that the ammonium cations are coordinated by the ether type oxygen atoms of the PPO chains backbone, whereas the amine groups of the urea linkage participate in the (PtCl3EtOH)(-) anion coordination. In situ Raman monitoring of Pt species decomplexation induced by immersion of hybrid matrix in water highlighted the specific participation of Pt ligands in interaction with the urea group and of NH4+ cations coordinated by ether type oxygen atoms in the formation of supramolecular interactions between the PPO chains. The electrospray mass spectrometry analysis of the Pt species released in water from the ureasil-PPO hybrid evidenced that the structure of the complex, NH4 (PtCl3 EtOH), incorporated in the matrix is totally preserved after delivery. Due to both well-known antitumoral and catalytic activities of Pt species, the results reported herein are of prime importance for further applications as drug delivery systems with optimized release pattern or as potential materials for new conceptual development of in situ catalyst delivery in homogeneous catalysis.